Praktik Akuntansi Sederhana Peternak Cacing : Sebuah Studi Fenomenologi di Desa Cabean Kabupaten Madiun Provinsi Jawa Timur - Nawangsari, Ajeng Tita; Cahyanti, Kharisma Galuh; Junjunan, Mochammad Ilyas (Prodi Akuntansi UIN Sunan Ampel Surabaya, 2022)
This study aims to answer the question of how simple accounting practices for worm farmers are based on the meaning of accounting for worm farmers. The research method used in this research is multiparadigm research with interpretive as the paradigm. The analysis tool uses transcendental phenomenology with data collection through interviews, observation and documentation. Then the data were analyzed using a set of transcendental phenomenological methods. Among others, analyzing noema, epoche, noesis, intentional analysis, eidetic reduction and finally discussing the results of the interview data. The results of this study are the accounting practices of worm breeders based on the meaning of accounting understood by the informants. The result of this interpretation is